ERCP stent as a nidus for CBD stone: post cholecystectomy status - Vinayaka, .; Haridarshan, S. J.; S., Venkatesh (International Surgery Journal, 2017)
Obstruction of common bile duct due to a ‘Forgotten stent’ causing stone formation is a rare entity, which is usually associated with cholangitis. A much rarer presentation is our case with an ERCP stent forming a nidus for stone formation in the common bile duct without any evidence of cholangitis or bile duct obstruction. A 66-year-old female patient with a previous history of laparoscopic cholecystectomy and common bile duct stenting done 2 years back presented with vague abdominal pain, nausea and vomiting without features of jaundice or cholangitis. She was diagnosed on imaging as a case of choledocholithiasis with two stents in the common bile duct. A failed ERCP to extract the stent and relieve obstruction necessitated open choledochotomy, stents removal, common bile duct clearance and choledochoduodenostomy. The rarity of this patient with an ERCP acting as a nidus for common bile duct stones without evidence of obstruction or cholangitis is something to be documented. Although rare, these complications must always be considered and considered a possibility due to which post-operative and post-endoscopic follow up, regular check-ups and timely removal of the stents is necessary to avoid unnecessary complications or a need for repeat procedures and surgery that results in greater morbidity.